Karakteristik Aerodinamika Flying Boat pada Ketinggian Ground Effect (Studi Kasus Model Remote Control Flying Boat Pada Ketinggian 0,2 m dan 1 m) - Sayuti Syamsuar (WARTA ARDHIA, 2015)
The paper presents an analysis of the flight performance and stability and control of a Flying Boat remote control model on the ground effect altitude. It begins with a three dimensional measurement of a Flying Boat remote control model by using a laser tracking photo camera and a drawing software. The 3 D model was drawn by solid drawing on the CATIA software. The 3 D model was analyzed by using computational fluid dynamics CFx AnSys due to the rectangular wing with dihedral configuration with NACA 23012 airfoil. The maximum takeoff weight is around 25.0 kg powered with a single engine propeller, 5.5 HP. The surface effect phenomena of the Flying Boat remote control model was simulated by using CFx omputational Fluid Dynamics software, AnSys with the airspeed, V = 35.0 knots and shows a good results at the altitude of 20.0 cm. The longitudinal static stability analysis provides a good result at 1.0 meter altitude. Simulations were performed to the PUNA “Alap alap” flight performance test during cruise at 7800 feet as data verification. The adaptive ground effect control system is solved by transfer function equation matrix. Keywords: Flying Boat, remote control model, ground effect altitude. Makalah ini berisikan analisis prestasi terbang dan kestabilan dari pesawat remote control model jenis Flying Boat pada ketinggian terbang ground effect. Pada awalnya, dilakukan pemotretan 3 D terhadap pesawat model Flying Boat menggunakan kamera laser beserta piranti lunak pendukung dan kemudian menggunakan solid drawing pada program CATIA. Model 3D dianalisis dengan menggunakan piranti lunak CFx AnSys untuk keseluruhan badan dan sayap dengan airfoil jenis NACA 23012. Karakteristik dinamik dari pesawat model dengan MTOW = 25.0 kg dengan power 5.5 HP terlihat dengan baik pada ketinggian terbang 20.0 cm dengan kecepatan, V = 35.0 knots. Sedangkan, analisis kestabilan statik matra longitudinal terlihat dengan respons waktu (t) yang baik pada ketinggian terbang 1.0 meter. Simulasi terbang menampilkan uji prestasi terbang pesawat nir awak PUNA “Alap alap” saat cruise pada ketinggian 7800 feet sebagai data verifikasi. Model matematika sistem Kendali Terbang Adaptif Ground Effect dianalisis dengan matriks persamaan fungsi transfer. Kata kunci: Flying Boat, remote control model, ketinggian terbang ground effect.